Attributes And Attitude Towards Crystal Methamphetamine Users: A Cross-Sectional Study - Nogdalla, Arwa Abdelmoneim Abdelaziz; Abd Alla, Magid Omer Mahmoud; Saga, Maria Badraldin Ali; Hassan, Ahmed Hazim Suliman; Ali, Duaa Abdelmonem Ahmed Elbasheer; Abdulraheem, Duaa Eihab Mohammedelfatih; Mamoun, Manasik Mamoun Mohamedahmed (International Journal of Medical Students, 2025)
BACKGROUND: Crystal methamphetamine (CM) is a powerful CNS stimulant, which causes a psychological disorder known as "ice psychosis," characterised by paranoid delusions, hallucinations, and strange, violent, or aggressive behavior. Permanent structural brain damage may also occur. It was reported that negative attitudes about medical conditions can directly affect patients' health and the quality of healthcare they receive, posing a major hurdle to healthcare delivery Not enough studies was conducted to investigate the attitude towards CM users among medical students, especially here in Sudan. Aim: In this study, we aim to determine the prevalence of negative attitudes towards CM users among medical students and investigate the correlation between certain attributes and that may affect thier attitude . METHODS: A cross-sectional study was conducted from March to July 2023 using an online questionnaire to examine the attitude of Sudanese medical students in Al-Neelain University towards CM users. The questionnaire was structured from a total of 31-items to asses other covariates including the demographics, experience with addiction, and previous CM use. RESULTS: The study included 300 students, 191(63.7%) of them are females. Age median 21.1 years (IQR=2.3). 153(51%) were in preclinical levels. Most students 274(91.3%) were single. 79(26.3%) of students had monthly income ≥ 100,000 SDG. Majority of students 252(84%) resided with family, in urban areas 266(88.6%). Students with GPA ≥ 4.1 were 137(45.7%). 12(4%) of students smokes. 48(16%) of students have a close one who uses CM. Only 5(1.7%) of students reported prior or current use of CM. Of those who use CM, only 2(0.7%) said they faced discrimination due to CM use. Students' attitudes mean score was 47.4 ± 6.8. Most students held a negative attitude against people who use CM, with majority reluctant to accept them. There was significant difference in attitude scores between females (Md= 47, n=191) and males (Md=49, n=109), p value = 0.002. Furthermore, those who used CM had a median of 38 in comparison to those who never used CM (Md=48), p value = 0.01. Indicating that males and non-users showed higher degrees of stigmatization towards people who use CM. CONCLUSION: Majority of students had negative attitude toward CM users with males and non-CM users representing most of the stigmatizing group. Therefore, stigma reduction initiatives and community educational programmes are required especially among higher stigmatizing group. Further in-depth studies are required at a national level.